Oviductal Glycoprotein 1 Promotes Hypertension by Inducing Vascular Remodeling Through an Interaction With MYH9. Issue 18 (29th September 2022) - Bai, Congxia; Su, Ming; Zhang, Yaohua; Lin, Yahui; Sun, Yingying; Song, Li; Xiao, Ning; Xu, Haochen; Wen, Hongyan; Zhang, Meng; Ping, Jiedan; Liu, Jing; et al.
Abstract : Background: Hypertension is a common cardiovascular disease that is related to genetic and environmental factors, but its mechanisms remain unclear. DNA methylation, a classic epigenetic modification, not only regulates gene expression but is also susceptible to environmental factors, linking environmental factors to genetic modification. Therefore, globally screening differential genomic DNA methylation in patients with hypertension is important for investigating hypertension mechanisms. Methods: Differential genomic DNA methylation in patients with hypertension, individuals with prehypertension, and healthy control individuals was screened using Illumina 450K BeadChip and verified by pyrosequencing. Plasma OVGP1 (oviduct glycoprotein 1) levels were determined using an enzyme-linked immunosorbent assay. Ovgp1 transgenic and knockout mice were generated to analyze the function of OVGP1. The blood pressure levels of the mouse models were measured using the tail-cuff system and radiotelemetry methods. The role of OVGP1 in vascular remodeling was determined by vascular relaxation studies. Protein–protein interactions were investigated using a pull-down/mass spectrometry assay and verified with coimmunoprecipitation and pull-down assays. Results: We found a hypomethylated site at cg20823859 in the promoter region of OVGP1 and plasma OVGP1 levels were significantly increased in patients with hypertension. This finding indicates that OVGP1 is associated with hypertension. In Ovgp1 transgenic mice, OVGP1 overexpression caused an increase in blood pressure, dysfunctional vasoconstriction and vasodilation, remodeling of arterial walls, and increased vascular superoxide stress and inflammation, and these phenomena were exacerbated by angiotensin II infusion. In contrast, OVGP1 deficiency attenuated angiotensin II–induced vascular oxidase stress, inflammation, and collagen deposition. These findings indicate that OVGP1 is a prohypertensive factor that directly promotes vascular remodeling. Pull-down and coimmunoprecipitation assays showed that MYH9 (nonmuscle myosin heavy chain IIA) interacted with OVGP1, whereas inhibition of MYH9 attenuated OVGP1-induced hypertension and vascular remodeling. Conclusions: Hypomethylation at cg20823859 in the promoter region of OVGP1 is associated with hypertension and induces upregulation of OVGP1. The interaction between OVGP1 and MYH9 contributes to vascular remodeling and dysfunction. Therefore, OVGP1 is a prohypertensive factor that promotes vascular remodeling by binding with MYH9.